Aspectos da dinâmica de emaranhamento em sistemas multipartidos e o interferômetro Mach-Zehnder com discriminador de que-caminho - Jose Geraldo Goncalves de Oliveira Junior (2011)
We investigate aspects, in various contexts, of entanglement and the wave particle duality. We show that the dynamics of tripartite systems which interact via one excitation exchange leads to a direct connection between entanglement sudden death and the appearance of genuine entanglement. We also show that this is valid (not with the same generality) also for a four partite system in the context of the double JaynesCummings model. Moreover we show that the entanglement dynamics in this case can be completely expressed in geometrical terms. Using the same system we show that by performing adequate Zeno like measurements it is possible to freeze, increase, or even revive the initial entanglement. This intriguing result is also associated to entanglement sudden death. As far as wave particle duality and entanglement are concerned we studied a particle going through an interferometer equipped with a whichway device. We quantified the quality of the probe and exhibit its connection with the availability of the whichway information provided by the probe system. When the probe system information is unaccessible only the particle character will be observed. We obtain limits for a good (quantum regime) and for a bad (classical regime) whichway detector (probe system). We used our results to interpret a recent experiment set up to test the quantumclassical border where the probe covers from the quantum to the classical limit. We showed that the experimental errors influenced the conclusion inferred form the data about having achieved the classical limit. Finally we analyze the Ramsey zones from the point of view of our findings and provide for a transparent physical interpretation. In this case the classical limit of the probe system is reached due to a source plus strong dissipation dynamics, which swaps whichway information to a system containing an infinite number of degrees of freedom, making thus sure that any whichway information becomes unavailable.